A Surveillance-Based Hepatitis C Care Cascade, New York City, 2017. (July 2018) - Moore, Miranda S.; Bocour, Angelica; Laraque, Fabienne; Winters, Ann
Objectives: The care cascade, a method for tracking population-level progression from diagnosis to cure, is an important tool in addressing and monitoring the hepatitis C virus (HCV) epidemic. However, little agreement exists on appropriate care cascade steps or how best to measure them. The New York City (NYC) Department of Health and Mental Hygiene (DOHMH) sought to construct a care cascade by using laboratory surveillance data with clinically relevant categories that can be readily updated over time. Methods: We identified all NYC residents ever reported to the DOHMH surveillance registry with HCV through June 30, 2017 (n = 175 896). To account for outmigration, death, or treatment before negative RNA results became reportable to the health department, we limited the population to people with any test reported since July 1, 2014. Of these residents, we identified the proportion with a reported positive RNA test and estimated the proportion treated and cured since July 2014 by using DOHMH-developed surveillance-based algorithms. Results: Of 78 886 NYC residents ever receiving a diagnosis of HCV and tested since July 1, 2014, a total of 70 397 (89.2%) had ever been reported as RNA positive through June 30, 2017; 36 875 (46.7%) had initiated treatment since July 1, 2014, and 23 766 (30.1%) appeared cured during the same period. Conclusion: A substantial gap exists between confirming HCV infection and initiating treatment, even in the era of direct-acting antivirals. Using this cascade, we will monitor progress in improved treatment and cure of HCV in NYC.